Comparison of cinnarizine/dimenhydrinate fixed combination with the respective monotherapies for vertigo of various origins: a randomized, double-blind, active-controlled, multicentre study - Hahn, Ales; Novotný, Miroslav; Shotekov, Penko M; Cirek, Zdenek; Bognar-Steinberg, Irene; Baumann, Wolfgang (Clinical drug investigation, 2011)
BACKGROUND AND OBJECTIVE: Vertigo may arise from dysfunction in the peripheral and/or the central vestibular system. Simultaneous activity of a medication at both sites will serve to improve the efficacy of antivertigo treatment. The aim of this study was to compare the efficacy and tolerability of a fixed combination of the peripherally acting cinnarizine (20 mg) plus the centrally acting dimenhydrinate (40 mg) with those of equally dosed monotherapies in the treatment of vertigo of various origins. METHODS: This prospective, randomized, double-blind, active-controlled, multicentre study included patients who assessed at least one vertigo symptom as being of at least medium intensity (≥2) on a 5-point visual analogue scale (VAS; ranging from 0 = not present to 4 = very strong) and who had pathological vestibulospinal movement patterns and/or nystagmus reactions. Patients were randomly assigned to receive either cinnarizine 20 mg/dimenhydrinate 40 mg as a fixed combination, cinnarizine 20 mg as monotherapy or dimenhydrinate 40 mg as monotherapy, each three times daily for 4 weeks. Patients were examined at baseline (t(0)), and after 1 week (t(1w)) and 4 weeks (t(4w)) of treatment. The primary efficacy endpoint was the decrease in mean vertigo score (MVS) at t(4w), which was calculated by averaging the total score for 12 individual vertigo symptoms, each assessed using the 5-point VAS. RESULTS: The study included 182 patients, of whom 177 were evaluable for efficacy. The mean ± SD reduction in MVS after 4 weeks of treatment with the fixed combination (-1.44 ± 0.56) was significantly greater than the reductions with each of the active treatments alone (cinnarizine -1.04 ± 0.53; dimenhydrinate -1.06 ± 0.56; p = 0.0001, both comparisons). Cinnarizine 20 mg/dimenhydrinate 40 mg as a fixed combination was associated with a significantly higher responder rate (78% of patients with MVS ≤0.5 at t(4w)) than the monotherapies. The odds ratios for MVS ≤0.5 at t(4w) in the cinnarizine or dimenhydrinate groups versus the fixed combination group were 0.345 and 0.214, respectively. The fixed combination reduced concomitant vegetative symptoms significantly more effectively than cinnarizine at both t(1w) (p < 0.05) and t(4w) (p < 0.01). Nine patients reported 15 adverse events (AEs) [three AEs for the fixed combination, six AEs each for cinnarizine and dimenhydrinate]. At t(4w) the tolerability of the treatments was rated as very good or good by almost all patients in all groups (fixed combination and dimenhydrinate 96.6% each; cinnarizine 98.3%). CONCLUSION: The fixed combination of cinnarizine 20 mg/dimenhydrinate 40 mg was an effective and well tolerated treatment for patients with vestibular vertigo of central and/or peripheral origin. The efficacy of the fixed combination exceeded that of each of the equally dosed active substances given as monotherapy, leading to higher responder rates, and showed a very good and comparable tolerability with a similar or even smaller rate of adverse events than the active substances given alone.
Keywords: vertigo; Drug Combinations; Male; Histamine H1 Antagonists; Dimenhydrinate; antagonisté histaminu H1; Cinnarizine; Adult; Aged; dospělí; Prospective Studies; mužské pohlaví; senioři; Vertigo; dvojitá slepá metoda; senioři nad 80 let; lidé; cinarizin; ženské pohlaví; Humans; Aged, 80 and over; dimenhydrinát; Double-Blind Method; Female; fixní kombinace léků; lidé středního věku; Middle Aged; prospektivní studie